Analisis Keputusan Menteri Agama Republik Indonesia tentang Pembatalan Keberangkatan Jamaah Haji : (Studi Pendekatan Qawa’id Ushuliyah dan Fiqhiyah dalam Lingkup Fikih Muamalah) - Asyari Hasan; Nofrianto; Muhammad Raja Perkasa Alam Harahap (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2021)
This paper analyzes the decision of the Minister of Religion of the Republic of Indonesia regarding the cancellation of the departure of the Hajj congregations with the qawa'id ushuliyah and qawa’id fiqhiyah approaches. This type of research is library research. The results that the qawa'id ushuliyah of the Minister of Religion's decision to cancel the departure of Indonesian Hajj congregations is QS Al-Maidah/5 verse 32 and the hadith of the Prophet Muhammad saw. which reads; If you get information about an epidemic in an area, don't enter that area. However, if the plague is where you live, then don't leave where you live. Meanwhile, the qawa'id fiqhiyah of the Minister of Religion's decision to cancel the departure of Indonesian congregations as follows: First, darul mafasidi muqaddamun ‘ala jalbil maṣalihi (to destroy damage is more important than doing good), Second, lã darãra walã dirãra (not allowed to harm, something dangerous and dangerous), Third, taṣarruful imam manutun bimaslahatil ra'iyyah (leadership policies must be based on the safety of the people), and Fourthly, al-ḍarãru yuzãlu (adversity must be eliminated). This study aims to find out the legal basis for the Minister of Religion in deciding to cancel the departure of the Hajj congregations in the last two years and to give views to the Indonesian people, especially the congregations whose departure has been postponed so that they are wise in responding to the Minister of Religion's decision.